2018
DOI: 10.1002/adfm.201805304
|View full text |Cite
|
Sign up to set email alerts
|

Toward Air Stability of Thin GaSe Devices: Avoiding Environmental and Laser‐Induced Degradation by Encapsulation

Abstract: Gallium selenide (GaSe) is a novel 2D material, which belongs to the layered III-VIA semiconductors family and attracted interest recently as it displays single-photon emitters at room temperature and strong optical nonlinearity. Nonetheless, few-layer GaSe is not stable under ambient conditions and it tends to degrade over time. Here atomic force microscopy, Raman spectroscopy, and optoelectronic measurements are combined in photodetectors based on thin GaSe to study its long-term stability. It is found that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 62 publications
3
75
0
Order By: Relevance
“…Additionally, the Raman spectra of GaSe crystals and exfoliated flakes do not present signatures attributed to Ga 2 Se 3 , Ga 2 O 3 , and amorphous/crystalline Se (a‐/c‐Se) modes, which are observed at ≈155, ≈200, and between 135–160 cm −1 , respectively. This indicates that the LPE of GaSe crystals in anhydrous IPA does not cause significant additional surface oxidation of the native material . This conclusion is further supported by X‐ray photoelectron spectroscopy (XPS) analysis (Figures S4 and S5 and Tables S2–S7, Supporting Information).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Additionally, the Raman spectra of GaSe crystals and exfoliated flakes do not present signatures attributed to Ga 2 Se 3 , Ga 2 O 3 , and amorphous/crystalline Se (a‐/c‐Se) modes, which are observed at ≈155, ≈200, and between 135–160 cm −1 , respectively. This indicates that the LPE of GaSe crystals in anhydrous IPA does not cause significant additional surface oxidation of the native material . This conclusion is further supported by X‐ray photoelectron spectroscopy (XPS) analysis (Figures S4 and S5 and Tables S2–S7, Supporting Information).…”
Section: Resultssupporting
confidence: 58%
“…Despite these encouraging driving factors, the PEC properties of GaSe are still experimentally uncharted. A certain reluctance to study the (photo)electrochemical properties of GaSe and other group‐III monochalcogenides undoubtedly originated from their tendency to undergo surface oxidation . The latter can occur either in a two‐step reaction: 1) GaSe + 1/4O 2 = 1/3Ga 2 Se 3 + 1/6Ga 2 O 3 followed by Ga 2 Se 3 + 3/2O 2 = Ga 2 O 3 + 3Se; or in a single‐step reaction: 2) GaSe + 3/4O 2 = 1/2Ga 2 O 3 + Se .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also explains why stoichiometric GaS crystals show greatly enhanced stability under laser and UV light. As a conjecture, the degradation could be greatly suppressed by encapsulation or inert gas protection, as have been shown to be effective in GaSe and GaTe . Second, the degradation rate of GaS 0.87 crystals varies with thickness.…”
mentioning
confidence: 93%
“…Jannatul et al used Raman spectroscopy to show that both Te metals and tellurium oxides form on the surface of layered GaTe crystals due to rapid oxidation . Recently, Zhao et al demonstrated that GaSe begins to degrade within hours on exposure to air into amorphous selenium, Ga 2 Se 3 , and Ga 2 O 3 . However, the degradation chemistry for each material is different, and more studies are needed for the increasing new members of 2D family.…”
mentioning
confidence: 99%